Exploratory Factorial Model of Perceived Safety in the COVID-19 Era - Fuentes, Jose Alfonso Aguilar; Crisanto, Gabriel Perez; GarcÃa Lirios, Cruz (Komunika, 2023)
The perception of the police action in the face of Covid-19 was the objective of this work. A cross-sectional, psychometric and correlational study was carried out with a sample of 100 students, considering their participation in the public health system as social servants or professional practitioners through a platform. A four-factor structure was found that explained 63% of the total variance, although the findings are only applicable to the sample, and its extension to other scenarios is recommended.